Analisis Masalah Dalam Kegiatan Proses Receiving Unit CBU Di Terminal Internasional PT. Indonesia Kendaraan Terminal - Wahyu Dwi Firmawan; Siti Sahara (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
Indonesia Kendaraan Terminal which is a company in the field of special terminal services for vehicle stacking. This research aims to find out what are the factors that affect the process of receiving activities of international terminal vehicles. In operational activities at the international terminal at PT Indonesia Kendaraan Terminal, there are several obstacles that can affect receiving activities. In the process of receiving vehicles at the international terminal gate, there are several factors that can hinder the receiving process and loading and unloading planning. This factor will certainly hinder the Receiving Process and Planning of Loading and Unloading so that it is inefficient and slows down the Receiving Process time at the gate and Load Planning activities in the international terminal field.